From competences to key competences in early Childhood Education. Comparative and upgrading of the competences in the curriculum - Rodríguez, Javier (2020)
From the Organic Law 2/2006, of May 3 (LOE), the concept, "basic competence", is introduced in our educational system. This requires schools at all levels of education, also Early Childhood Education, educational and non-care,to readjust the organization of teaching -learning contexts, methodologies and didactic strategies.The work presented below makes a comparative study to analyze and unify the configuration of the curriculum of early childhood education based on competences (LOE, 2006 and LOMCE 2013) and itpresents the need for an update that, without it, leaves the stage of Early Childhood Education, once again, as dispensable and outside of important decisions, in addition to the novelties of the other stages of our educational system.This article has the objective of facilitating the teachers of Early Childhood Education the adaptation of their didactic program or curricular project to the new key competences, marked by the LOMCE, and thus be able to put into practice the new didactic and methodological approaches that this law defends and that should apply to the entire education system. Even counting on the duality of having to maintain the structureof the previous law, LOE, for some specific aspects and at the same time adapt it to the new modifications that do affect this "EDUCATIONAL" stage of Early Childhood Education. We write "Educational" in capital letters because we consider that this stage is the priority, formative, emergent, constructive and essential basis of the teaching-learning process of our students and their families.